Improvement of the social requirements of the quality-social accountability-health and safety integrated management system - Romeo Denuntzio (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
The paper has the goal to present a method to improve the social requirements of the quality-social accountability-health and safety integrated management system with the social requirements of the Busines Social Compliance Initiative (BSCI) Code of conduct because SA 8000 standard have to fulfil all the requirements of BSCI Code of conduct. The method used was to make a correspondence between the SA 8000 standard requirements and the BSCI Code of conduct requirements because the requirements of the BSCI Code of conduct are more detailed in some areas than the requirements of SA 8000 standard which establish the social requirements of the quality-social accountability-health and safety integrated management system. It was established on this way the detailed suplimentary requirements from the BSCI code of conduct which have to be added to the requirements of SA 8000 standard to reach the full compliance with the social requirements of the BSCI Code of conduct.The conclusions of the paper is that the suplimentary detailed requirements improve the implementation of quality-social accountability-health and safety integrated management.
Keywords: 330; Management system; Social accountability; Business Social Compliance Initiative (BSCI)